Informacja jako czynnik przewagi konkurencyjnej regionu - Wich, Urszula (Information as a Factor of the Region's Competitive Advantage, 2008)
The article concerns the importance of information for the contemporary economy. It also presents the development tendencies of teleinformation services in the European Union countries. The development of teleinformation techniques was assessed and the place of our country among the member states was defined against this background. The analysis of propagating teleinformation services in the context of other development factors, conducted in the regional cross-section, was the basis for evaluating regional differentiations in this domain. It also allowed for demonstrating soothing influence of these high technology services upon the traditional division of regions and their significant role in stimulating the development and forming the competitive advantage of the regions.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 197-206